Macroeconomic factors affecting bank deposits An applied study on private traditional banks operating in Syria - حميشه رؤى; منى بيطار (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research aims to study the impact of macroeconomic variables on bank deposits in traditional private banks operating in Syria, during the period from the first quarter of 2011 to the second quarter of 2020. To achieve the objective of the study, the impact of some macroeconomic variables represented in (GDP, money supply, real interest rate, and unemployment) on the dependent variable (total bank deposits) was studied, with a number of controlling variables such as (bank size, profitability, index Global Terrorism), using the Autoregressive Distributed Lags models. The study concluded that there is a positive and significant effect of the studied macro variables on bank deposits in the long term. In the short term, there was a negative and significant impact on the GDP and the real interest rate on bank deposits. As for the money supply and the unemployment, they did not have any effect on the dependent variable.